Global burden and trends of pelvic organ prolapse associated with aging women: An observational trend study from 1990 to 2019 - Wang, Bo; Chen, Yingying; Zhu, Xiaoran; Wang, Tian; Li, Mei; Huang, Yibao; Xue, Liru; Zhu, Qingqing; Gao, Xiaofan; Wu, Mingfu (Frontiers in Public Health, 2022)
Purpose: Worldwide, about 40% of women will experience pelvic organ prolapse (POP), and this proportion is expected to increase with the aging of the population. We investigated the global, regional, and national burden of POP from 1990 to 2019, by age and social-demographic index (SDI). Patients and Methods: Data were extracted from the Global Burden of Disease (GBD) 2019 database for 195 countries and territories between 1990 and 2019. The estimated annual percentage change (EAPCs) was used to explore age-standardized incidence rate (ASIR) and age-standardized disability-adjusted life years (AS-DALYs) trends were presented, along with their corresponding 95% uncertainty intervals (UI). Results: In 2019, the global ASIR and AS-DALYs for POP were 316.19 [95%UI: 259.84-381.84] and 10.37 [95%UI: 5.79-17.99] per 100,000 population, respectively. Moreover, from 1990 to 2019, the ASR of both showed a downward trend, and EAPCs were -0.46 [95%CI:-0.52 to -0.4] and -0.53 [95%CI:-0.58 to -0.47], respectively. In addition, DALYs of POP also showed a downward trend in most regions and countries with high SDI. From 1990 to 2019, the global incidence rate and DALYs rate were highest in the 65–75 and ≥60 age groups, respectively. Conclusion: Over the past three decades, the incidence and DALY of POP have been decreasing from 1990 to 2019. However, POP remains a major health problem, especially among females in less developed countries. Primary and secondary prevention measures of POP should be integrated into the practice of healthcare professionals dealing with aging women.